Association between BMI and inflammation among diabetic polyneuropathy patients - Tayebeh Mottaghi; Fariborz Khorvash; Farzin Khorvash; Mohammadreza Maracy; Majid Kheirrollahi; Gholamreza Askari (International Journal of Preventive Medicine, 2019)
Background: Inflammation is defined as body tissues response to harmful stimuli. Obesity-related inflammation leads to increased risk chronic diseases including diabetic polyneuropathy (DPN). The present study was performed to determine association between body mass index (BMI) and inflammatory markers including erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) in DPN patients. Methods: In this cross-sectional study, 200 DPN patients with a mean (SD) of age 58.76 (9.53) years were selected. All patients completed the questionnaire including demographic data and chronic disease history. In addition, anthropometric measures and clinical laboratory tests were taken. Multivariate linear regression was used to detect the association between BMI, CRP, and ESR levels. Results: BMI was associated with increase in ESR and CRP levels (β-ESR = 4.67, P < 0.001 and β-CRP = 0.71, P < 0.001). Also, this association remained after adjustment for other different variables. Conclusions: These findings indicate that higher BMI is related to increase inflammatory markers including CRP and ESR in DPN patients. Therapies for DPN and reducing inflammation should target the weight loss among obese patients.